Pengaruh Karakteristik Komite Audit terhadap Manajemen Laba (Studi pada Perusahaan Manufaktur Sektor Konsumsi yang Terdaftar di BEI Periode 2020 – 2022) - Simamora, Lamtiur; Siboro, Danri T; Saribu, Ardin Dolok (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The study aims to find out the impact of the characteristic audit committee of manufacturing companies with profit management on the consumer sector listed in the EIB (Indonesian Stock Exchange) period 2020-2022. The sampling technique in this study was carried out using purposive samplings so 37 companies were obtained. From the results of the test understanding it can be concluded that only the first hypothesis (audit committee competence) has proved to have a positive and significant influence on Profit Management, while the size of the audit committee and audit meetings of the committee frequency have no influence and do not syphnify gegen variable dependen. This is demonstrated through a test-t result that shows a meaningful relationship to a variable with a 5% dimension significance.